RELATIONSHIP BETWEEN LIGNIN CONTENT AND QUALITY OF Pinus taeda SEEDLINGS1 - Dranski,João Alexandre Lopes (2015)
ABSTRACT The essay objective was to correlate lignin content resulting from tigmomorphogenesis induced by stem swaying with survival and post-planting growth of P. taeda seedlings. Seedlings were subjected to daily frequencies (0, 5, 10, 20 and 40 movements) of stem swaying for 60 days. By the end of the treatments, we determined lignin content of below and aboveground seedling tissues. Four replicates per treatment were planted in a area cultivated with pines. Ninety days after planting, survival and increments of seedling height, stem diameter and stem volume were quantified. Application of 20 stem swayings increased lignin in both below and aboveground plant tissues. Outplanted seedling survival was reduced with 40 stem swayings while growth increments were increased with both 10 and 20 stem swayings. Lignin content from belowground plant tissues was positively correlated with outplanted seedling survival while lignin from aboveground tissues correlated with height and stem volume increments. P. taeda seedlings with higher lignin content have higher survival chances after planting.